(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
A Modular Armed Advanced Robotic System based on face recognition is intended for military applications identifies the unidentified individuals in border area or conflict zones or in any comparable location, and conducts obstacle detection, bomb detection and implements gun aiming system. Wi-Fi connection is carried to send the message to the receiving system. This function is done by algorithm or manually with the assistance of Lab view or SSH (Secured Shell) software installed in recipient system. This method is done out utilizing Raspberry Pi board with ARM cortex A53 CPU and Arduino Uno microcontroller (AtMega328P). The hardware comprises the ultrasonic sensor, Bluetooth device, wireless camera, DC (Direct Current) servo motor, and mechanical gripper. Unique single ultrasonic sensor is automated to pursue the article, and complete the article localization. A human-machine interface is manufactured to remotely operate the transportable robot. Through wireless connection and camera, the investigation of a minute and punishing environment may be carried out. Hardware explanation language is utilized in the controller enterprise and the fringe I/O (input/output) circuit. Human machine interface is done via C language which can be useful in various future studies.